40 Weeks of Gestation is as High-Risk Gestation as 41 Weeks in Low-Risk Pregnancies - Aqsa Ikram ul haq, Shama Bashir,Nargis Shaban,Nadia Sadiq, Fatima Chaudhry Inayat ,Jaweria Faisal, Aqsa Ikram ul haq, Shama Bashir,Nargis Shaban,Nadia Sadiq, Fatima Chaudhry Inayat ,Jaweria Faisal (Journal of Rawalpindi Medical College, 2020)
Introduction: Postdate pregnancy is associated with a higher frequency of obstetrical complications and perinatal morbidity. The incidence of meconium-stained amniotic fluid is 30% at 40 weeks which is very high. This study aimed to find out the need for fetal surveillance and delivery in our population, keeping in view that 40 weeks of gestation is as high risk as 41 weeks gestation in low-risk pregnancies. Material and Methods: The study was conducted at Obstetrics & Gynecology Department, Unit-II, Holy Family Hospital, and Rawalpindi from 16 February to 15 August 2019 after ethical clearance. Postdate pregnant women from 40 to 41 weeks who meet study criteria were enrolled in the study. We divided participants into two groups. Group A (40 to 40+6 weeks of gestation) while group B had Group B (41 to 41+6 weeks of gestation). Results: A total of 236 postdate mothers presented of which 148(62%) were in group A while 88 (38%) were in group B. Mean gestational age in our study was 40.88 ± 0.71 weeks. overall vaginal delivery, cesarean delivery, and meconium stained liquor were found in 75.84%, 24.16%, and 35.17% patients respectively. 82 (34.7%) participants presented with meconium-stained liquor meconium-stained liquor with women in group B has a higher frequency of meconium-stained liquor, 45 (30.41%) in group A and 37 (42.04%) in group B, P-value 0.069. rate of vaginal delivery was 71.62% in group A and 82.95% in group B which was statistically significant. P-value 0.049 Conclusion: High percentage of meconium-stained liquor was observed in the study population. Frequency of vaginal delivery increases if postdate women waited till 41 weeks. 30% of women at gestation age 40 to 40+6 have meconium-stained liquor which shows almost 1/3 of pregnant ladies are exposed to the compromised fetal status which is a considerable risk. This increases further as the gestation age advances. Appropriate interventions should be taken at 40 weeks in low-risk pregnancies to avoid perinatal risk.